ASPARAGINASE INDUCED SINUS VEIN THROMBOSIS IN AN ADULT YOUNG ALL PATIENT - Beyza OLUK (Elsevier, 2021)
Objective: Asparaginase has a very important role in ALL treatment among increasing of remission rate and duration. Multiple side effects prevent its regulatory use. Asparaginase reduce antithrombin 3, heparin cofactor II, protein C and plasminogen synthesis. By the way, P-selectin, PAI 1, tissue factor activity, and vWF antigen levels increase. Hypofibrinogenemia may be a marker of of hemostasis disturbances and decreased protein synthesis. Case report: A 25-year-old male patient with acute T-cell lymphoblastic leukemia diagnosis was initiated on induction chemotherapy according to augmented BFM protocol. After 4 weeks, remission was confirmed. During consolidation with the third dose of standard L-asparaginase of 10000 units, headache, nausea and vomiting started and confusion developed. Biochemical investigations, PT, aPTT were within normal limits. Fibrinogen was 92 mg/dL and D-dimer was high.Contrast-enhanced MRI showed a thrombus occluding. Methodology: the superior sagittal sinus. He was intubated and followed up in the intensive care unit due to a rapid decline in the Glasgow score and epileptic seizures. Correction of fibrinogen with cryoprecipitate anticoagulation treatment contributed to symptoms improvement. unfortunately, asparaginase was removed from the protocol. During maintenance therapy, he has had severe COVID-19 pneumonia and during this time he did not experience any thrombosis related complications. Results: Asparaginase therapy is associated with low antithrombin and fibrinogen levels and 7% of thrombosis rate. Previous studies showed that, in ALL patients, thrombosis occurred far more frequently during cycles that contained asparaginase than those that did not. Conclusion: Therefore, studies have investigated the role of fresh frozen plasma or cryoprecipitate supplementation to reduce the thrombohemorrhagic risk of therapy. Retrospective studies suggest antithrombin concentrates may have a beneficial effect on the outcomes of adults treated with asparaginase for ALL.